Enhancing Image Encryption Using Double Random Permutation and Memristive Chaos: A Combined Approach (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Since the secure transmission of optical digital images has emerged as a major area of academic interest, the topic of information security in photonics environments has garnered increasing attention. In this work, we present a hybrid encryption strategy based on the memristor hyperchaotic system and a double random transform for pictures in the frequency and spatial domains. This study presents a robust and secure picture encryption technique that combines compressed sensing, double random phase encoding (DRPE), and Lorenz mapsWe also make double-random-phase masks using Lorenz maps, which enhance the unpredictability and key sensitivity, thereby enhancing the security of the encryption method. . Experimental studies utilize a range of performance metrics, such as the PSNR, NPCR, MSE, and SSIM, to show the value of the suggested approach.